Supply Chain and Marketing Analysis of Seaweed (Kappaphycus alvarezii) in Nunukan - Hakim, Rusmini; Kantun, Wayan; Nurbaya, Nurbaya (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Seaweed is a superior commodity for aquaculture and is a raw material for export. Sustainability of exports requires sustainable seaweed production to ensure the sustainability of raw materials to fulfil market demand from buyers and consumers. In this regard, this research aims to analyze the supply chain, margins and marketing efficiency of Kappaphycus alvarezii seaweed cultivated by the community in Nunukan District, North Kalimantan. This research is classified as a quantitative type of research with a survey method using an interview method through the distribution of questionnaires to seaweed business actors. The results of the research show that information was obtained about the Kappaphycus alvarezii seaweed supply chain through three marketing channels, namely (1) channels from seaweed farmers to collectors and consumers, (2) channels from seaweed farmers to consumers and (3) channels from collectors to consumers . Seaweed production produced by farmers does not have a minimum production quantity standard so that the seaweed produced can be sold at any time to collectors according to a predetermined price agreement. Meanwhile, there are differences in seaweed marketing margins between respondents in the marketing network, and price differences at the collector level cause price differences at the consumer level. The resulting marketing efficiency is at an efficient level (â‰¤ 50%). Seaweed marketing in Nunukan is classified as efficient because the share received by seaweed farmers as producers is below 50%. The efficiency of seaweed marketing depends on the level of marketing margin and the share received by seaweed farmers.